Language and persuasion in Islamic preaching - Rahman, Hafiz Mahmood (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This study examines the linguistic characteristics and persuasive techniques utilized in Islamic sermons, with the objective of enhancing our comprehension of language's function in religious discourse. The study shows the different parts of these sermons that make them more convincing by looking at word choices, sentence structures, rhetorical techniques, emotional appeals, logical arguments, religious authority, and story-telling methods. An analysis comparing various situations and speakers demonstrates differences in language characteristics and persuasive techniques. The results of this study are good for both linguistics and Islamic studies because they give a thorough look at the language used in Islamic sermons and show how important it is for people from different fields to work together to understand religious discourse. More research needs to be done on the linguistic aspects of religious discourse in a variety of settings and traditions. This will help us understand how language affects how beliefs and attitudes are formed in religious settings.